KEY PROVISIONS OF THE ORGANIZATION OF ACCOUNTING OF GOODS AND SETTLEMENT OPERATIONS WITH SUPPLIERS - Гладий, Ирина; Дзюба, Оксана; Мастер, Людмила (SWorldJournal, 2020)
The article highlights the aspects of accounts payable to suppliers for goods from a legal point of view and, at the same time, the recognition of debts in the accounting system according to national and international accounting standards. It is proposed